2013
DOI: 10.1167/iovs.12-11322
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting the Ocular Surface Response to Desiccating Environmental Stress

Abstract: Ocular surface dye staining increases in response to desiccating stress. Baseline ocular surface dye staining, tear meniscus height, and blink rate predict severity of ocular surface dye staining following exposure to a desiccating environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Regarding meteorological conditions, previous studies suggested humidity, wind speed, and sunshine duration as potential risk factors of DED [27-32]. Our results showed that lower humidity and longer sunshine duration were associated with DED before and after adjusting for covariates.…”
Section: Discussionsupporting
confidence: 57%
“…Regarding meteorological conditions, previous studies suggested humidity, wind speed, and sunshine duration as potential risk factors of DED [27-32]. Our results showed that lower humidity and longer sunshine duration were associated with DED before and after adjusting for covariates.…”
Section: Discussionsupporting
confidence: 57%
“…6,7 This may be a result of the desiccating stress that air drafts, low humidity, and decreased blinking have on the ocular surface. This stress leads to increased tear instability, evaporation and osmolarity, which contributes to a downstream cascade of events that promote production of inflammatory mediators (cytokines and matrix metalloproteinases), epithelial apoptosis and loss of conjunctival goblet cells.…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, reduced tear production from aging, use of systemic medications with anticholinergic effects or autoimmune conditions such as Sjögren syndrome and rheumatoid arthritis may contribute to development of environmentally induced dry eye. 10,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…While this approach allows for detailed analysis of the timing and pattern of orbicularis oculi electromyographic (OOemg) activity, electrical stimuli necessarily by-pass normal sensory transduction mechanisms. Tear osmolarity is a key factor in predicting severity in dry eye disease (Sullivan et al, 2010, Alex et al, 2013), while abnormal light sensitivity is a common symptom in dry eye (Pflugfelder, 2011) and blepharospasm (Adams et al, 2006, Hallett et al, 2008), conditions well associated with abnormal control of eyeblinks. Trigeminal sensory nerves that supply the eye and periocular tissues project centrally to terminate in two spatially discrete regions, the trigeminal subnucleus interpolaris/caudalis transition (Vi/Vc) and the trigeminal subnucleus caudalis/upper cervical cord junction (Vc/C1) regions (Marfurt, 1981, Marfurt and Del Toro, 1987, Marfurt and Echtenkamp, 1988, Panneton et al, 2010).…”
mentioning
confidence: 99%